H. J. Morgenthau, le débat entre idéalistes et réalistes et l'horizon politique de la théorie des relations internationales : une interprétation critique - Thibault, Jean-François (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1997)
It is a truism to state today that the idealist-realist debate represents a foundational moment of great importance for the discipline of international relations that had defined and set the problematic that will occupy her latter. In those circumstances, the works of Hans f. Morgenthau occupied a privileged posture because he contributed more than anyone else to grasp what makes the originality and specificity of that « new » domain of study. The metatheoretical examination of that idealist-realist debate and of the strategic position that it occupied in the theoretical thinking of Morgenthau allowed us to enlighten anew one crucial moment in the analytical constitution of international relations. Retrospectively this kind of metatheoretical examination throws critical light on difficulties faced by theoretical activities in that discipline.